The Impact of "Informer on Site" in Disaster Management - Nazli, Nadian Nisa; Sipon, Sapora; Ali, Asiah; Omar, Muhammad Nur Wafi (International Journal of Interactive Mobile Technologies (iJIM), 2017)
"Informer on site" is a smart phone application that provides a new channel for the community to raise complaint regarding a disaster in Malaysia. It is focused on disseminating information on disasters such as floods, landslides, typhoons, and haze within a short time in a reliable manner. This application could prove to be an effective and efficient tool to facilitate smooth communication and allows for faster emergency response. This paper discusses the the impact of "Informer on Site" in disaster management.